ANALISIS SEMIOTIKA ROLAND BARTHES PADA KAVER BUKU SIMBOLISME DALAM BUDAYA JAWA KARYA BUDIONO HERUSATOTO - Daniartana Hukubun, Lejar (Kartala, 2024)
The book cover is one of the media to introduce the contents of a book to the general public."Symbolism in Javanese Culture" is a book by Budiono Herusatoto, published by Hanindita in2001. This book explains various topics, namely: Culture and Symbolism, The History of theJavanese Tribe, The Philosophy of Javanese Life, The Symbolic Actions of the Javanese People,Further Developments.The cover of this book appears very attractive and balanced in terms of color, illustration,typography, composition, and layout. This research aims to uncover the meaning contained inthis cover through Roland Barthes' semiotic theory, examining the systems of denotation,connotation, and myth. A qualitative descriptive process technique is used as the researchmethod. The results of this research will provide information about the relationship of signspresent on this book cover, including the interconnection of all components on the cover.